Spontaneous live recurrent ectopic pregnancy after ipsilateral partial salpingectomy leading to tubal rupture - Abraham, Cynthia (Int J Surg Case Rep, 2014)
INTRODUCTION: Ectopic pregnancy accounts for 1–2% of all pregnancies in the United States. The most common site of implantation for an ectopic pregnancy is the fallopian tube. We present the first case describing a recurrent ectopic pregnancy with a fetal heartbeat after ipsilateral salpingectomy that led to tubal rupture. PRESENTATION OF CASE: The patient presented with abdominal pain approximately six weeks after her last menstrual period. Seven years prior to presentation, a laparoscopic partial right salpingectomy had been performed for a tubal ectopic pregnancy. Physical exam was significant for diffuse abdominal tenderness and guarding. Ultrasonography revealed a right tubal pregnancy with a fetal pole and a fetal heart rate that was calculated to be 108 beats per minute. Free fluid was also noted. 1.5 l of hemoperitoneum was subsequently evacuated and the right fallopian tube remnant with the ectopic pregnancy was removed. Pathology of the tubal remnant showed immature chorionic villi and fetal parts. DISCUSSION: The mechanism by which a recurrent ectopic pregnancy after ipsilateral salpingectomy occurs is unclear, but is theorized to be secondary to contralateral fertilization and/or tubal recanalization that may occur due to inadequate diathermy. CONCLUSION: Physicians should be aware that ectopic pregnancies may not only occur repeatedly but may also present a typically. We recommend when performing a salpingectomy that efforts be undertaken to minimize the length of the tubal remnant and to assure adequate coagulation of tissue so as to reduce the risk of recurrence.